Technology Enable Literacy Education through Open and Distance Learning (ODL) in Bangladesh: An Approach - Alam, MS; Alam, MS (Journal of Agriculture & Rural Development, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Bangladesh is a densely populated country with a population of 130 million. In Bangladesh the Government and non-Government organizations have taken sufficient initiative to increase the literacy rate but the significant development is yet to achieve. Despite the various steps taken by the Government, the literacy rate stands at 62 percent and, as such, the goal to educate all remains more or less as elusive as ever. Sophisticated technological development in the education world changes the pattern of role and responsibility of learners and teachers and creates more opportunities of learning. Using the virtual image of the Distance Education system there emerges a new horizon of innovativeness with its unlimited possibilities to resolve a very long felt need of eradicating illiteracy and developing human resources (HR) in the globe. Technologies are used in distance education and which can create a forceful impact to accelerate mass literacy, gender balance and also help develop human resources in the pursuit of acquiring different branches of knowledge and skill along with technical and vocational aspects to meet the thirsty need of the time. This paper addresses the issues for developing strategies for technology based literacy programme. It also highlights to identify the parameters for developing an appropriate technology based quality materials for literacy programme. Key words: Appropriate technology, distance education, virtual image, illiteracy, quality material. DOI = 10.3329/jard.v5i1.1449 J Agric Rural Dev 5(1&2), 1-6, June 2007